Translation of Islamic culture into Arabian architecture. - Omar, Mona A. E. (Curtin University, 2000)
In the past, researchers in the field of art and architecture have searched for a definition of Islamic architecture, its history and its social meaning. This study focuses on the Islamic culture of the Arab world and its influences on the architecture of the region, giving an overview of contemporary architecture in the Arab world, its situation, cultural crisis and hope for the future.This research aims to identify the principal characteristics of Islamic architecture, which embody the needs and demands of Muslims according to their Islamic teachings. Muslims form one of the biggest communities in the world, which is suggested to be more than one fifth of the world's population, about one and half billion.This community has special architectural needs related to their religious teachings, traditions and culture, because Islam is not only a religion, it is a complete way of life, which covers all social, political, economic, educational, cultural, hygienic, and behavioural aspects.For a great number of people, the concept of Islamic architecture denotes tangible characteristics of some architectural features like Mashrabiah, arch, dome, or any other architectural pattern that distinguishes this typical style of architecture. But, Islamic architecture is more than just a spectacle of domes and minarets; it is a deep expression of a rich culture that has unified countries across the globe.In the last fifty years, contemporary architecture of the Muslim world in general, and the Arab world in particular, has been exposed to several outside influences that have eventually caused it to be alienated from its particular sense of identity and, thus, to lose its character. It is believed that such matter requires immediate attention towards attempting a "revival process" by uncovering the bases and principles of Islamic architecture, as manifested throughout Islamic history. These principles could be integrated and molded into the contemporary architecture of the Arab world, which reflects a rather complicated and, sometimes, contradicting set of values.The aim of this study is to develop an appropriate definition for Islamic architecture of the Arab world in terms of Islamic teachings and doctrine.Associated with this aim, this research will include within its scope:Understanding Arabian Islamic culture, traditions and environment and how they have affected architectural design.Translating some principles from Islamic doctrine, which can be applied to architectural practice, and to recognize Muslims' architectural needs and demands, according to Islamic teachings.Developing architectural standards that satisfy Muslims architectural needs and a definition of what, in an Islamic context, could be considered as successful Arabian Islamic architecture.Analyzing to what extent contemporary architecture meets Muslims' needs, according to their Islamic teachings by undertaking a Case Study of pre-Modern and contemporary architecture in Egypt.